Error traps in acute pain management in children. Issue 9 (7th July 2022) - Vecchione, Tricia M.; Agarwal, Rita; Monitto, Constance L.
Abstract: Providing effective acute pain management to hospitalized children can help improve outcomes, decrease length of stay, and increase patient and parental satisfaction. Error traps (circumstances that lead to erroneous actions or undesirable consequences) can result in inadequately controlled pain, unnecessary side effects, and adverse events. This article highlights five error traps encountered when managing acute pain in children. They include failure to appropriately assess pain, optimally utilize regional anesthesia, select suitable systemic analgesics, identify and treat medication‐related side effects, and consider patient characteristics when choosing medication or dosing route. These issues are easily addressed when the clinician is cognizant of ways to anticipate, identify, and mitigate or avoid these errors.